OP0333 Survival in anca associated vasculitides: a retrospective multicentric analysis in northern italy. (12th June 2018) - Felicetti, M.; Monti, S.; Bond, M.; Berti, A.; Padoan, R.; Paolazzi, G.; Brunori, G.; Quartuccio, L.; Caporali, R.; Schiavon, F.
Abstract : Background: Patients affected by ANCA associated vasculitides (AAV) show lower survival than general population, even if the mortality decreased significantly in the last decade. Objectives: Aim of our study is to analyse the early mortality (within 6 months) and the long-term survival in a multicentric Italian cohort of AAV patients. Methods: we identified all patients affected by AAV, diagnosed from 1995 until 2017, followed routinely in four vasculitis referral centres in Norther Italy. We enrolled patients with diagnosis of granulomatosis with polyangiitis (GPA) and micro polyangiitis (MPA), fulfilling EMA algorithm or CHCC 2012 definitions, with complete survival data at last follow up. The analysis focused on early mortality, long-term survival and their predictors. Results: We enrolled 200 AAV patients (F/M 110/90, Caucasian 98%) with a median age at diagnosis of 54.6±15.2 years. 157 (78.5%) were affected by GPA and 43 (21.5%) by MPA. Data about ANCA antibodies were available in 181 patients and 157 (87%) resulted ANCA positive: 100 c-ANCA/PR3, 56 p-ANCA/MPO and one with double specificity PR3-MPO-ANCA. During the follow up period [53 28–100 months], we registered 21 (10.5%) deaths, 6 (28.5% of all mortality) within 6 months after diagnosis: 9 patients died due to infectious complications, 1 due to hepatic cancer, 1 due to end stage heart failure, 1 due to massive cholestasis and 9 due to unknown causes. Early mortality was significantly associated with a higher frequency of alveolar haemorrhage (p=0.01; OR 11.1 IC95% 2.1–60.1) and respiratory failure (p<0.001, OR 28.3 95% CI: 4.7 to 170.6). The long-term survival, analysed with Kaplan-Maier method, did not show significant differences between GPA and MPA patients, while a significant poorer survival was observed in p-ANCA/MPO patients than c-ANCA-PR3 and ANCA negative patients (Log rank test: p=0.04). At univariate analysis of baseline data, deceased patients resulted older at disease onset (p=0.001) with more comorbidities (p<0.001) and presented at diagnosis a higher frequency of respiratory failure (p=0.002, OR 7.1 IC95% 2.2–22.2) and renal insufficiency (p=0.003, OR 4.7 95% CI: 1.6 to 13.7). No significant differences were noted in term of infections/year, relapses/year and cancer development. Conclusions: In this large cohort of Italian patients we confirm a higher short and long-term survival in AAV patient than reported in literature. Nevertheless, up to one third of deaths occurred within 6 months after diagnosis and infection diseases resulted the most frequent cause of death. Moreover, our data confirm the prognostic importance of ANCA pattern and the poor outcome of patient with severe lung and renal involvement. Disclosure of Interest: None declared